(untitled) (Bangladesh Journal of Livestock Research, 2021)
This survey was carried out to know the existing livestock farming system along with socioeconomic conditions in livestock communities in two different selected hilly areas under Bandarban and Cox’s Bazar District. Data were collected based on the farmer’s personal information, livestock and poultry production system, problems and prospects of livestock production and socio-economic status of commodity through a pre-structured questionnaire. The result revealed that there was no significant (P˃0.05) different in family size, age of the farmers but have significant (P˂0.05) different in illiteracy and occupation of the two villages. According to the land distribution pattern, there was no significant (P˃0.05) different in land size and land ownership but have significant (P˂0.05) different in cultivable and fellow land of the farmers in selected areas. The majority of the farmers have indigenous (native) type livestock and the cattle population was higher in Tulatuli (plain area) than in Adarshogram (hilly area) and it differed significantly (P˂ 0.05). In Adarshogram and Tulatuli villages, most of the farmers (79% and 80.43%) had separate housing facilities for their livestock species and they sold their livestock and poultry species in their local market. About 85.90% of farmers depended on natural sources as feed for their animals and only 14.10% purchased feed for their animals. About 71.50% of farmers faced animal feed crisis during the summer season followed by the rainy 19% and winter (9.50%) seasons. There was no significant (P˃ 0.05) different in the body weight of cattle, goats and sheep and milk production of cattle between the two villages. Most of the farmers (89.45%) depended on natural mating for breeding purposes and only 10.55% of farmers practiced artificial insemination. Cattle showed repeat heat which was significantly (P˂ 0.05) differ in the two villages. There was no significant (P˃0.05) different in calf/kid care after calving of the selected villages. About 72, 74% and 14, 17% and 42.42, 71.28% were affected warm in cattle, PPR in goats and ND in poultry, respectively between the two villages. About 60% and 58% of birds/animals were affected during the rainy season and most of the farmers 82% and 92% disposed of their dead birds/animals in the pit of the two villages. The result showed that average non-farm income (Tk.136929.44) was higher than farm income (Tk.50632.15) and average gross income per farmer per year was higher (Tk. 204739.37) in Tulatuli than Adarshogram (Tk.170383.74) but net income was in opposite direction. Results also showed that skill-ness about animal and poultry rearing, concentrate feed availability, vaccination facility and lack of pasture land had the main problems of the farmers for livestock and poultry rearing in selected two villages and significantly (P˂ 0.05) differed. Most of the farmers are interested in rearing cattle farming, followed by poultry, sheep, goats and pigeons in selected villages. It may be concluded that raising awareness, providing vaccination, making sustainable technology available, providing technical support for current stock to increase livestock production, and enhancing the livelihoods of local hill peoples. Bang. J. Livs. Res. Vol. 28 (1&2), 2021: P. 29-41